2020
DOI: 10.1016/j.heliyon.2020.e04862
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PEGylated iron oxide nanoparticles on sheep ovarian tissue: An ex-vivo nanosafety study

Abstract: Today, nanotechnology plays an important role in our ever-continuous quest to improve the quality of human life. Because of their infinitesimal size, nanostructures can actively interact and alter cellular functions. Therefore, while the clinical benefits of nanotechnology may outweigh most of the associated risks, assessment of the cytotoxicity of nanostructures in respect to cells and tissues early in product development processes is of great significance. To the best of our knowledge, no such assessment has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Finally, the particles were PEGylated in a PEG-silane (Merck, Germany) solution. After synthesis, the resulting IONP@Si@PEG were characterized with Dynamic Light Scattering (DLS), Zeta-potential (SZ-100 Nanoparticle Analyzer – Horiba, Japan), X-Ray Diffraction (XRD) (Philips PW 1730, Germany), Fourier Transform Infrared Spectroscopy (FTIR) (Thermo Nicolet AVATAR 370 FTIR) and Transmission Electron Microscopy (TEM) (Leo 912 Ab Omega, Zeiss) operated at 120 kV and the toxicity of IONP@Si@PEG evaluated in our pervious study [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the particles were PEGylated in a PEG-silane (Merck, Germany) solution. After synthesis, the resulting IONP@Si@PEG were characterized with Dynamic Light Scattering (DLS), Zeta-potential (SZ-100 Nanoparticle Analyzer – Horiba, Japan), X-Ray Diffraction (XRD) (Philips PW 1730, Germany), Fourier Transform Infrared Spectroscopy (FTIR) (Thermo Nicolet AVATAR 370 FTIR) and Transmission Electron Microscopy (TEM) (Leo 912 Ab Omega, Zeiss) operated at 120 kV and the toxicity of IONP@Si@PEG evaluated in our pervious study [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…SOD Assay : To measure SOD and CAT activity, the kidneys were weighed and homogenized in phosphate-buffered saline at 4°C and then centrifuged, and the supernatant was kept for assessments. The measurement of SOD activity was done by pyrogallol auto-oxidation effect and the absorbance was measured at 570 nm [42].…”
Section: Methodsmentioning
confidence: 99%
“…For female gametes, after culturing early follicles enclosed in sheep ovarian tissues in vitro, Karimi et al (2020) showed that uncoated iron oxide nanoparticles induce oxidative stress on the ovarian cortex while tissues treated with PEGylated iron oxide nanoparticles exhibit no significant change in oxidative stress.…”
Section: Concerns About the Use Of Nanomaterialsmentioning
confidence: 99%
“…For female gametes, after culturing early follicles enclosed in sheep ovarian tissues in vitro , Karimi et al (2020) showed that uncoated iron oxide nanoparticles induce oxidative stress on the ovarian cortex while tissues treated with PEGylated iron oxide nanoparticles exhibit no significant change in oxidative stress. M. Ghorbani et al (2019) showed that green synthesized zinc oxide nanoparticles and commercial zinc oxide nanoparticles have negative effects on preantral follicles through increasing the production of free radicals, reducing the expression of estradiol and testosterone, reducing expression of GDF‐9 and BMP‐15, as well as increasing the expression of Foxo1 and VNN1.…”
Section: Concerns About the Use Of Nanomaterialsmentioning
confidence: 99%